Pengaruh Pijat Oksitosin Pada Nifas Post Sectio Cesarea Terhadap Pemberian ASI Neonatus Dini - Astari, Ni Kadek Yunita Ari; Suindri, Ni Nyoman; Rahayu, Sri (Midwifery Care Journal, 2025)
Â The coverage of exclusive breastfeeding in Bali Province in 2022 has decreased to 64.92%. This coverage is still below the national exclusive breastfeeding coverage target of 80%. One of the contributing factors is the lack of milk production in postpartum mothers. Oxytocin massage is a non-pharmacological therapy that is applied with massage to the back area along the spine which aims to provide a relaxing sensation and can facilitate milk production. The purpose of this study was to determine the effect of oxytocin massage therapy on postpartum mother post caesarea sectio with breastfeeding in early neonates. This type of research is an experiment using posttest only control group design. The number of samples was 26 samples in the treatment group and 26 samples in the conventional control group that met the inclusion criteria. The sampling technique used is purposive sampling with interview data collection techniques. Data analysis in this study was univariate and bivariate analysis using the Independent t-test. The results of this study showed that P Value 0.000 < 0.05 this shows that there is an effect of oxytocin massage therapy on postpartum cesarean section with breastfeeding in early neonate. For breastfeeding mothers, the results of this study can be used as a reference in the application of oxytocin massage therapy to facilitate to increase milk production and increase maternal comfort through assistance from health workers, husband and families.